Evaluation Study of the Active Compounds and Antioxidant Activity of Lavender Extract - Mohannad Rasheed H. AL-Zaydi; Weaam Ahmed Alwan; Sara Munther Mubder; Dorees Taher Hasan; Aya Azam Jamal (Academia Open, 2025)
General background: Medicinal plants have long been recognized for their therapeutic properties due to their bioactive compounds. Specific background: Lavender (Lavandula spp.) is widely used for its aromatic, medicinal, and preservative properties, but comprehensive analyses of its leaf extract's phytochemical profile and antioxidant potential remain limited. Knowledge gap: While numerous studies have explored lavender essential oils, fewer have examined the secondary metabolites and antioxidant capacity specifically from leaf-based alcoholic extracts. Aims: This study aimed to evaluate the active compounds and antioxidant activity of the alcoholic extract of lavender leaves by identifying its chemical composition and quantifying key bioactive metabolites. Results: Phytochemical screening revealed the presence of phenolic compounds, flavonoids, tannins, glycosides, alkaloids, terpenes, and sterols. The extract showed the highest concentration of total phenolics (25.32 mg/100 g) and the lowest of glycosides (0.076 mg/100 g). Antioxidant assays confirmed its capacity to scavenge free radicals effectively. Novelty: This study provides detailed evidence of the potent antioxidant activity of lavender leaf extracts, contributing new insights distinct from flower-based evaluations. Implications: These findings support the potential development of lavender leaf-based natural antioxidants for pharmaceutical and nutraceutical applications. Highlights: Identified seven major classes of secondary metabolites in lavender leaf extract. Highest antioxidant activity linked to phenolic and flavonoid content. Demonstrated potential for pharmaceutical and nutraceutical applications. Keywords: Lavender Plant, Active Compounds, Antioxidant Activity